Verification of Methods for Determining The Antioxidant Capacity of Matoa (Pomitea Pinnata) Leaves Ethanol Extract By Uv-Vis Spectrofotometry - Made Surya Pramana Mahardika; I Komang Eka Wiratnyana Putera; I Gede Arie Mahendra Putra (SEAS (Sustainable Environment Agricultural Science), 2025)
The testing laboratory of the Faculty of Agricultural Technology, Udayana University is a laboratory that conducts tests for various kinds of analysis, one of which is the antioxidant capacity test. Antioxidant capacity can be measured by UV-Vis spectroscopy method using DPPH that is determined spectrophotometrically through percent absorbance attenuation. The number of studies that focus on matoa leaf extract antioxidants is one reason to improve the quality of laboratory quality by conducting validation and verification tests of the methods used. The objectives of this study was to verify or validate the method of determining the antioxidant capacity content of matoa leaf ethanol extract by UV-VIS spectrophotometry used in the laboratory. The data analysis employed is non-statistical, utilizing descriptive analysis, where the data obtained from the research are presented and interpreted descriptively to provide an overview of the observed facts. The verification and validation parameters evaluated in this study included the Limit of Detection (LOD), Limit of Quantitation (LOQ), precision, accuracy, and linearity. Based on the study results, the linear regression equation obtained was y = 0.0042x - 0.0119 with a value of r = 0.9989, precision value with %RSD <2/3CvH, percent recovery in the range of 93.60 - 98.36%, detection limit of 1.73 ppm and limit of quantification of 5.76 ppm. Based on the verification results, the method satisfies the required standards and is suitable for application in the testing laboratory of the Faculty of Agricultural Technology at Udayana University